MOBILITAS TENAGA KERJA PERTANIAN ANTAR SEKTOR EKONOMI DI KECAMATAN LAPE KABUPATEN SUMBAWA - Gina Tri Utami; Fuad Alfarizi; Elly Karmeli (Jurnal Ekonomi & Bisnis, 2022)
The aim of this study were: 1) to determine the labor mobility of farmers in various economic sectors in the village Lape; 2) to determine the household income of the various economic sectors in the village Lape; and 3) to determine the contribution of revenue from the various sectors of the economy on household income. The research was conducted in the village of Lape, using descriptive methods and data collection is done by observation and interview techniques. Determination of the respondents conducted by quota sampling technique. The results showed that: (1) the amount of labor mobility that occurs an average of 73.58 HKO in various sectors of the economy at a time of planting season. Labor mobility is divided into four economic sectors, namely agriculture amounted to 63.58 HKO, the mining sector by 6.56 HKO HKO service sector of 2.51 and 0.93 HKO trade sector. (2) household income of farmers by an average of Rp 13,781,785, - per one growing season. (3) Contributions revenue contributed by the farmers on household income is different in each sector. In the agricultural sector accounted for 73.44%, 21.67% mining sector services sector 4.22% and 0.67% of trade sector.